2010
DOI: 10.1175/2010jpo4356.1
|View full text |Cite
|
Sign up to set email alerts
|

Deep Equatorial Ocean Circulation Induced by a Forced–Dissipated Yanai Beam*

Abstract: A complex pattern of zonal currents below the thermocline has been observed in the equatorial Pacific and Atlantic Oceans. The currents have typical speeds from 10 to 15 cm s 21 and extend as deep as 2500 m. Their structure can be divided into two overlapping parts: the equatorial deep jets (EDJs), centered on the equator and alternating in the vertical with a wavelength of several hundred meters, and the Equatorial Intermediate Current system (EICS), composed of currents with large vertical scale and alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 50 publications
8
103
0
Order By: Relevance
“…6, the "flanking jets" are much stronger than the off-equatorial zonal jets noted earlier. Ascani et al (2010) have suggested that these jets are maintained by Yanai waves, generated at the surface (possibly by instability of the energetic near-surface flow field forming tropical instability waves: von Schuckmann et al, 2008;Jochum et al, 2004), which break at depth. The jets show considerable variability (see Fig.…”
Section: Advectionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, the "flanking jets" are much stronger than the off-equatorial zonal jets noted earlier. Ascani et al (2010) have suggested that these jets are maintained by Yanai waves, generated at the surface (possibly by instability of the energetic near-surface flow field forming tropical instability waves: von Schuckmann et al, 2008;Jochum et al, 2004), which break at depth. The jets show considerable variability (see Fig.…”
Section: Advectionmentioning
confidence: 99%
“…Their strengths have been quantified using subsurface drift trajectories from floats (Maximenko et al, 2005;Ollitrault et al, 2006) and repeated shipboard sections . Such currents have been reproduced by idealised process modelling (Mé-nesguen et al, 2009;Ascani et al, 2010;Qiu et al, 2013),…”
Section: Introductionmentioning
confidence: 99%
“…These currents are divided into two groups: a group of currents trapped on the equator that change sign with depth with a wavelength of about 500 m (the Equatorial Deep Jets) and a group of currents of large vertical scale that alternate with latitude every 1-2 ı between 10 ı S and 10 ı N (the Equatorial Intermediate Currents). Here we define this set of deep zonal currents as EICS (note, this definition is different from the one used in Ascani et al [2010]). …”
Section: Introductionmentioning
confidence: 99%
“…Because these important currents are not well resolved neither in coarse resolution Earth System Models ( Figure 1b) nor in eddy-resolving ocean circulation models [Ascani et al, 2010], questions remain about the impact of this missing circulation on simulated nutrients and oxygen in the EEP.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a barotropic zonal mean flow, which depends only on latitude, a necessary condition for an increase in width is a positive curvature of the zonal flow at the equator. In the equatorial Atlantic Ocean, the Equatorial Intermediate Current (EIC), a large verticalscale westward flow, is flanked by eastward jets at 28N/S called the North and South Intermediate Counter Currents (NICC and SICC, respectively; Richardson and Fratantoni 1999;Gouriou et al 2001;Ascani et al 2010;Greatbatch et al 2012). These currents can create the necessary environment for a reduced meridional gradient of ambient vorticity and hence a widening of the EDJs.…”
mentioning
confidence: 99%